2001
DOI: 10.1074/jbc.m104687200
|View full text |Cite
|
Sign up to set email alerts
|

The Position of the α and β Subunits in a Single Chain Variant of Human Chorionic Gonadotropin Affects the Heterodimeric Interaction of the Subunits and Receptor-binding Epitopes

Abstract: The glycoprotein hormone family represents a class of heterodimers, which include the placental hormone human chorionic gonadotropin (CG) and the anterior pituitary hormones follitropin, lutropin, and thyrotropin. They are composed of common ␣ subunit and a hormone-specific ␤ subunit. Based on the CG crystal structure, it was suggested that the quaternary subunit interactions are crucial for biological activity. However, recent observations using single chain glycoprotein hormone analogs, where the ␤ and ␣ sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The generation of variants in the presence or absence of a linker sequence to space the tethered subunit domains, as well as switching their relative position, enabled to generate SC gonadotropin analogs with differences in the conformation (Argos, 1990;Ben-Menahem et al, 2001Garcia-Campayo and Boime, 2001;Grinberg et al, 2008;Sugahara et al, 1995Sugahara et al, , 1996b. Interestingly, gonadotropin analogs, mostly SC variants but also mutated heterodimers and nonpeptide mimetics, with a conformation that is different from that of the wild-type heterodimer, bound to the cognate receptor and stimulated cAMP formation, which is a key signaling mediator for steroidogenesis (Ben-Menahem et al, 1997;Fralish et al, 2003;Garcia-Campayo and Boime, 2001;Grossmann et al, 1997;Heikoop et al, 1997;Jackson et al, 1999;Maclean et al, 2004;Moyle et al, 1987;Perlman et al, 2003;Sato et al, 1997;Sugahara et al, 1995;van Straten et al, 2002;Weenen et al, 2004;Xing et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The generation of variants in the presence or absence of a linker sequence to space the tethered subunit domains, as well as switching their relative position, enabled to generate SC gonadotropin analogs with differences in the conformation (Argos, 1990;Ben-Menahem et al, 2001Garcia-Campayo and Boime, 2001;Grinberg et al, 2008;Sugahara et al, 1995Sugahara et al, , 1996b. Interestingly, gonadotropin analogs, mostly SC variants but also mutated heterodimers and nonpeptide mimetics, with a conformation that is different from that of the wild-type heterodimer, bound to the cognate receptor and stimulated cAMP formation, which is a key signaling mediator for steroidogenesis (Ben-Menahem et al, 1997;Fralish et al, 2003;Garcia-Campayo and Boime, 2001;Grossmann et al, 1997;Heikoop et al, 1997;Jackson et al, 1999;Maclean et al, 2004;Moyle et al, 1987;Perlman et al, 2003;Sato et al, 1997;Sugahara et al, 1995;van Straten et al, 2002;Weenen et al, 2004;Xing et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory and others have also reversed the order of subunit tether to N-␣-CTP-␤-C (YhCG3; Refs. [19][20][21]. This analog bound LHR poorly, but activated the receptor efficiently, thus uncoupling the two activities (19).…”
mentioning
confidence: 96%
“…Using monoclonal antibodies, single-chain hCG (N-␤-␣-C) was shown to retain biological activity when some of the native quaternary interactions at the interface between the subunits were disrupted by mutation (26). However, complete disruption of subunit interactions, as in the single chain N-␣-␤-C (without linker), causes nearly complete loss of activity (21). From these elegant studies, it is apparent that native tertiary and quaternary structure are not a prerequisite to biological activity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We and others have shown that biologically active fusion proteins of hCG could be constructed in the manner N-hCG --C (Narayan et al 1995, Sugahara et al 1995, Heikoop et al 1997, Schubert et al 2003 and N--CTP-hCG -C (Narayan et al 2000a, Sen Gupta & Dighe 2000, Ben-Menahem et al 2001. These studies were expanded to include yoked hCG-rat LHR complexes (YHR) of the form, N-hCG --CTP-LHR-C (Wu et al 1996) and N--hCG -LHR-C (Narayan et al 2000a), resulting in ligand-mediated constitutive receptor activation.…”
Section: Introductionmentioning
confidence: 99%